1998
DOI: 10.1046/j.1365-2753.1998.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Audit in transfusion practice

Abstract: Given the growing concern for the safety, cost and adequacy of blood supply, there is an increasing need for appropriate blood product utilization. Despite a number of consensus guidelines for the transfusion of allogeneic blood products, inappropriate blood transfusion continues. We discuss the quality assurance process for improvement in transfusion therapy including audit of blood transfusion. Audits identify areas of problems in transfusion practice which can be corrected by education of doctors, formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
0
12
1
2
Order By: Relevance
“…9,10 Internal audit aims at proper selection of blood components for patients and avoiding their overuse. 11,12 Due heavy population demand for blood and blood components are more and increasing day by day. But the supply of blood and blood components are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Internal audit aims at proper selection of blood components for patients and avoiding their overuse. 11,12 Due heavy population demand for blood and blood components are more and increasing day by day. But the supply of blood and blood components are limited.…”
Section: Discussionmentioning
confidence: 99%
“…In various studies [10][11][12][13][14] it is revealed that for sustained improvement in practice, prospective monitoring must be continued indefinitely. It is difficult due to lack of staff and more time consuming.…”
Section: Discussionmentioning
confidence: 99%
“…[9] In Maharashtra, all blood-banks and blood-storage centers have to maintain a record on blood collection and distribution. All regional blood-banks supplying blood units to blood-storage centers record the information on the number of blood units supplied, blood group of the supplied blood units, and dates of issue and expiry.…”
Section: Discussionmentioning
confidence: 99%
“…These facts in detail have been prescribed and proved in the studies done by McCullough J and Steeper TA et 5,6 al and Silver H and Tahhan HR et al According to them, the regular data updates and working upon it of the individual blood bank is proved to be an important aspect of the quality control mechanism in any blood bank, which is same as that in any other ins tu ons or organiza ons. Studies done by 7,8 Brandia K et al and Joshi GP et al has the common conclusion, sta ng about the easy and appropriate use of blood transfusion units and the blood components is on a high demand for its easy availability of sophis cated blood banking services. Thus, the blood bank should be regular enough for upda ng and fulfilling the requisites of this vital and life saving products.…”
Section: Discussionmentioning
confidence: 99%